High-quality draft genome sequence of the Thermus amyloliquefaciens type strain YIM 77409T with an incomplete denitrification pathway. Issue 1 (December 2016) - Zhou, En-Min; Murugapiran, Senthil; Mefferd, Chrisabelle; Liu, Lan; Xian, Wen-Dong; Yin, Yi-Rui; Ming, Hong; Yu, Tian-Tian; Huntemann, Marcel; Clum, Alicia; Pillay, Manoj; Palaniappan, Krishnaveni; et al.
Abstract Thermus amyloliquefaciens type strain YIM 77409T is a thermophilic, Gram-negative, non-motile and rod-shaped bacterium isolated from Niujie Hot Spring in Eryuan County, Yunnan Province, southwest China. In the present study we describe the features of strain YIM 77409T together with its genome sequence and annotation. The genome is 2, 160, 855 bp long and consists of 6 scaffolds with 67.4 % average GC content. A total of 2, 313 genes were predicted, comprising 2, 257 protein-coding and 56 RNA genes. The genome is predicted to encode a complete glycolysis, pentose phosphate pathway, and tricarboxylic acid cycle. Additionally, a large number of transporters and enzymes for heterotrophy highlight the broad heterotrophic lifestyle of this organism. A denitrification gene cluster included genes predicted to encode enzymes for the sequential reduction of nitrate to nitrous oxide, consistent with the incomplete denitrification phenotype of this strain.